Static phase gradient metasurface antenna enabling synergistic radiation-scattering function integration - Xin Wang; Qin Chen; Junlin Wang; Yifan Hou; Chengshuang Zhu; Yunsheng Guo; Yang Wang; Tao Zhou (New Journal of Physics, 2025)
This paper presents a metasurface antenna with both radiation and scattering characteristics. First, a symmetric slotted patch antenna unit is designed and its operating frequency is tuned to the 8.4–9.4 GHz (11.2%) range. Subsequently, incorporating the principles of propagation phase, this study designs eight phase gradient metasurface units by varying the length of the I-shaped metallic arms on the unit surface, achieving a complete 2 π phase coverage. By arranging such metasurface antenna units in different configurations, functions such as radar cross-section (RCS) reduction, vortex wave generation, and beam deflection can be achieved in the operating frequency band. To achieve the integration of the radiation and scattering functions, a power divider is designed to feed the metasurface antenna. This approach achieves a unified system capable of transmitting and manipulating electromagnetic waves in multiple ways. According to the simulation and measurement results, the meta-plane antenna, after forming an array, can operate in the frequency band up to 8.5 GHz–10.6 GHz (22%), and the radiation gain in the frequency band can reach 20.1 dBi–21.4 dBi, which can effectively reduce the RCS in and out of the frequency band, as well as realize the functions of vortex wave generation and beam deflection, and, in short, the meta-plane antenna achieves the integration of radiation and scattering functions.